Matthew Weinstein. - Simmons, Laurie (Bomb (0743-3204))
An interview with the artist Matthew Weinstein is presented. Particular focus is given to his work in acrylic painting and video. Additional topics discussed include how he utilizes computer animation in his work, insights on his artistic techniques and his collaborations with professional actors and musicians.